Association of genetic variations in PTPN2 and CD122 with ocular Behcet's disease. Issue 7 (3rd March 2018) - Zhang, Qi; Li, Hua; Hou, Shengping; Yu, Hongsong; Su, Guannan; Deng, Bolin; Qi, Jian; Zhou, Chunjiang; Kijlstra, Aize; Yang, Peizeng
Abstract : Background: Protein tyrosine phosphatases (PTPs) play critical roles in human autoimmunity. Previous studies found that PTPN2 may be the key regulatory factor in the T-cell-mediated immune response. PTPN2 regulates the Janus kinase/signal transducers and activators of transcription pathway by inhibiting signalling via the interleukin (IL)-2 receptor (CD122). An association between genetic variations in PTPN2 and CD122 with ocular Behcet's disease (BD) has not yet been addressed and was therefore the purpose of this study. Methods: A two-stage case–control study was performed in 906 patients with ocular BD and 2178 healthy controls. Genotyping analysis of 11 single nucleotide polymorphisms was carried out. The expression of PTPN2 in peripheral blood mononuclear cells (PBMCs) was quantified by real-time PCR and cytokine production was measured by ELISA. Results: The frequency of the GG genotype of PTPN2-rs7234029 was significantly lower in patients with ocular BD (p=1.94×10 −5, pc =8.34×10 −4, OR=0.466). Stratification according to gender showed that rs7234029 was significantly associated with BD in men. A stratified analysis according to the main clinical features showed that rs7234029 was significantly associated with genital ulcers, skin lesions and a positive pathergy test. No association could be detected between BD and CD122 gene polymorphisms. Functional studies showed that rs7234029 GG genotype carriers had a higher PNPT2 mRNA expression level than those which carrying the AA or AG genotype, and a decreased secretion of IL-17 and tumour necrosis factor-alpha was seen by PBMCs from GG carriers. No significant difference could be detected concerning IL-1β or IL-6 production by stimulated PBMCs between the different genotype groups. Conclusions: This study shows that a PTPN2-rs7234029 polymorphism is associated with ocular BD and is strongly influenced by gender. In addition, our results suggest that the genetic association with PTPN2 may involve the regulation of PTPN2 mRNA expression and cytokine secretion.